GOOD CORPORATE GOVERNANCE DAN RASIO KEUANGAN DALAM PENINGKATAN PROFITABILITAS - Defi Istiani; Ana Kadarningsih (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2023)
The financial performance of a company shows how successful the business is. Financial performance shows how good the operational condition of the business is from a financial perspective, whether it is growing or declining. The four objectives of this research are as follows: to find out how liquidity and solvency ratios affect financial performance, to find out how activity and liquidity ratios affect financial performance, and finally, to find out to what extent the implementation of good corporate governance affects financial performance. In this research, 81 manufacturing companies in the food and beverage subsector listed on the Indonesia Stock Exchange from 2020 to 2022 were included in the population. Purposive sampling technique was used to ensure that the sample complies with the requirements. There are 26 companies with 312 data processed from samples collected according to the criteria. This research was carried out using multiple linear regression analysis along with the coefficient of determination test, normality test and descriptive statistical test. The analysis tool uses SPSS version 24. The results of the study can be partially formulated that the variable liquidity ratio has a positive effect on financial performance. While the solvency ratio variable does not have a significant effect on financial performance. The variable activity ratio and good corporate governance have a negative and significant effect on the company's financial performance.